KEPASTIAN HUKUM JAMINAN KREDIT FIDUSIATERKAIT HAK CIPTA KONTEN YOUTUBE - Yulistiawaty, Yulistiawaty; Nasseri, Jelly; Basuki, Basuki (SINERGI : Jurnal Riset Ilmiah, 2024)
Based on Law No. 28 of 2014 concerning copyright, video content uploaded through the Youtube platform can be included in creations that are protected by law, because they are included in cinematographic works and can be categorized as intangible movable objects and can be used as objects of fiduciary security. In practice, both banks and non-bank financial institutions find it difficult to accept Youtube video content as an object of guarantee for financing agreements, this is because creditors do not feel that Youtube video content is an object that provides legal certainty if the debtor defaults. How does the fiduciary credit guarantee apply to youtube content Copyright? What is the legal certainty of fiduciary credit guarantee regarding youtube content Copyright? The theory used in this research is the theory of legal certainty Gustav Radbruch and The Theory of legal guarantees J.Satrio. The method used in this study is normative juridical research, namely legal research literature or secondary data with sources of primary, secondary and tertiary legal materials equipped with interviews. The research approach used is the approach of legislation and case approach and legal material collection techniques carried out by identifying and inventorying the rules of positive law, literature books, journals and other legal sources. For Technical Analysis of legal materials is carried out by systematic legal interpretation and methods of legal construction. From the results of the study, it can be concluded that youtube content is included in cinematographic works and can be categorized as intangible movable objects and can be used as objects of fiduciary security as Article 16 Paragraph (3) of the copyright law, but in practice there is still a need for arrangements and regulations related to the receipt of collateral in the form of intellectual property. So as to provide legal certainty to the banking institutions and non-banking institutions